Pomen organizacijske kulture za uspešnost storitvenih organizacij - Vrčon-Tratar, Nataša (Akademija MM, 2002)
Organizational culture as an internal consciousness of organizations as well as crucial determinant of their employee behaviour serves undoubtedly as an important phenomenon of scientific research especially from the perspective of its contribution to the performance of organizations as potential factor of their comperatitive advantage. In the paper authors discuss some aspects of organizational culture and try to find out if the right orientation and the strenght of organizational culture contribute signifficantly to the efficient realization of organizational objectives and to overall effectiveness. Special attention is paid to the importance of culture in service organizations employees as the creators of so called soft elements of the offers play decisive role in customer perception of the offers value and at the time serve as the key generator of the competitive positioning of service organizations.
Keywords: konkurenčnost; marketing; organizacijska kultura; podjetja; poslovna uspešnost; storitve; teorija organizacije; trženje